LOCAL THERAPY OF THE NOSE FURUNCLES IN CHILDREN - E.S. Kovalets; E.Yu. Radtsig; M.R. Bogomil'skii; A.P. Kitaigorodskii (Union of pediatricians of Russia, 2011)
Paper is devoted to a common pathology in pediatric otorinolaryngology - nose furuncle. The authors present their own data on the occurrence of the nose furuncle in children, as well as share their own experience in treating this disease. The clinical efficacy of local therapy in treatment of an abscessed nose furuncle in children and bacteriological efficacy in the treatment of nasal carriage of St. aureus recurrence in children with nasal furuncle has been studied. Good tolerability and high efficacy of this drug in the treatment of the nose furuncle in children when applied topically was marked. Key words: nose furuncle, Staphylococcus aureus, treatment, children. (Pediatric pharmacology. - 2011; 8 (6): 25-29).